Strategi Meningkatkan Kesadaran Menabung pada Anak-Anak Sejak Dini di Dusun II Desa Pantai Labu Kecamatan Pantai Labu - Muning Ariani; Himatul Ulia Br Sitepu; Nurul Feni Saputri; Pani Akhiruddin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
UMSU KKN activities in Dusun II, Pantai Labu Village focus on developing a simple financial education program for elementary school students through the concept of saving. This program is motivated by the importance of instilling the habit of saving from an early age to form a wise young generation in managing finances. One of the innovations implemented is the Savings Challenge, which is designed to increase students' motivation to save consistently. This competition involves all students, where they compete to save with a certain target during a predetermined period. The purpose of this program is to teach students about the importance of saving regularly and introduce the concept of simple financial planning. The method used is a participatory approach, where students are actively involved through games, stories, and group saving challenges. In addition, collaboration with teachers and parents is also an important part in ensuring the sustainability of the program. The results of this program show an increase in students' motivation to save, both at school and at home. Children not only understand the importance of saving, but are also motivated to achieve their short-term financial targets. In addition, this program also received support from teachers and parents, who felt a positive impact on students' behavior in managing their money.